Ruang Lingkup Organisasi Dan Arsitektur Komputer - Dewangga Andira Sulaeman; Ismah Nurul Sya’bani; M. Ashof Azria Azka; Didik Aribowo (Politeknik Kampar, 2023)
In computer system architecture, the role of the processor cannot be separated as the main component in the operation of the computer operating system. CPU (Central Processing Unit), or commonly called a processor, is a part in the form of a rectangular chip or integrated circuit, the main component of a computer system, which functions to control computer operations, supported by other departments. The unit of processing speed is Mega Heartz or 1000 MegaHeartz. The higher the value, the faster the process runs on the computer. Processor development has progressed so rapidly from year to year that even pioneers such as Intel and AMD are still competing to this day.